Pengaruh Motivasi Internal dan Kepemimpinan Transformasional Terhadap Kinerja Pegawai Pada Dinas Sosial Kota Lubuklinggau Dengan Variabel Spiritual Intelligence Sebagai Variabel Moderasi - Revi Isnabilla Hoirunisa; Dheo Rimbano; Dewi Anggraini; reviisnabilla@gmail.com (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of internal motivation and transformational leadership on employee performance with spiritual intelligence as a moderating variable at the Lubuklinggau City Social Service. The background of this study is based on the importance of the role of human resources in achieving organizational goals and the decline in employee work productivity as seen from monthly performance achievement data. This study uses a quantitative approach with an associative method. The sample used was all 31 employees of the Lubuklinggau City Social Service, with a saturated sampling technique. Data were collected through observation, interviews, documentation, and questionnaires with a Likert scale. Data analysis was carried out using SmartPLS 3.0 software. The results of this study are expected to provide empirical evidence that internal motivation and transformational leadership have an effect on employee performance, and spiritual intelligence can moderate this effect. This study also provides theoretical contributions to the development of human resource management science and practical benefits in improving the performance of public organizations.